2021
DOI: 10.1038/s41598-021-97192-9
|View full text |Cite
|
Sign up to set email alerts
|

The complex evolution of the metazoan HSP70 gene family

Abstract: The metazoan 70-kDa heat shock protein (HSP70) family contains several members localized in different subcellular compartments. The cytosolic members have been classified into inducible HSP70s and constitutive heat shock cognates (HSC70s), but their distinction and evolutionary relationship remain unclear because of occasional reports of “constitutive HSP70s” and the lack of cross-phylum comparisons. Here we provide novel insights into the evolution of these important molecular chaperones. Phylogenetic analyse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The phylogenetic trees were constructed using the neighbor-joining method by MEGA 11.0 software ( , accessed on 7 February 2022) with bootstrap values from 1000 replicates indicated at each node with the following parameters: p -distance and pairwise deletion. Nomenclature of all HSP genes was completed based on the amino acid sequence similarities and phylogenetic analysis, and the HSP70s were renamed according to the new nomenclature which was proposed by Yu et al [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…The phylogenetic trees were constructed using the neighbor-joining method by MEGA 11.0 software ( , accessed on 7 February 2022) with bootstrap values from 1000 replicates indicated at each node with the following parameters: p -distance and pairwise deletion. Nomenclature of all HSP genes was completed based on the amino acid sequence similarities and phylogenetic analysis, and the HSP70s were renamed according to the new nomenclature which was proposed by Yu et al [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…They have further been classified into either inducible HSP70s or constitutively expressed HSC70s, but until recently, their evolutionary relationship remained elusive, mainly due to the lack of cross-phylum comparisons. However, a recent in-depth phylogenetic study reviewing 125 complete HSP70/HSC70s genes from a wide range of species across different phyla has clarified the complex evolution of this gene family [ 32 ]. According to this study, HSP70 family members associate with mitochondria and the endoplasmic reticulum form two monophyletic groups ( Figure 3 ).…”
Section: The Essentials Of Emi and Cmamentioning
confidence: 99%
“…Interestingly, an inter-clade comparison of the synonymous and nonsynonymous substitution rates revealed that all HSP70/HSC70 family members are under strong purifying selection [ 32 ]. The presence of such a purifying selection was already reported for mammalian [ 33 ], nematode [ 34 ], molluscan [ 35 ], and protist [ 36 ] HSP70/HSC70 genes.…”
Section: The Essentials Of Emi and Cmamentioning
confidence: 99%
See 1 more Smart Citation
“…In vertebrates, there are two main forms of HSP70s: several members exhibit constitutive expression patterns, while others are induced by various stresses that disrupt proper protein folding and they are regulated by HSF1. The evolutionary histories of HSP70s, and especially of the inducible forms, are quite complex with events of convergent evolution and gene duplication among others; hence, a new nomenclature for their classification has been proposed [ 23 ], Yu et al, 2021. The HSPs are closely associated with the cellular response to a variety of stressors, and they are not merely linked to the heat stress, as it was initially believed [ 24 ].…”
Section: Introductionmentioning
confidence: 99%